Compressive strength of fly-ash-based geopolymer concrete at elevated temperatures - Shaikh, Faiz; Vimonsatit, Vanissorn (John Wiley and Sons Ltd., 2014)
This paper presents the compressive strength of fly-ash-based geopolymer concretes at elevated temperatures of 200, 400, 600 and 800 °C. The source material used in the geopolymer concrete in this study is low-calcium fly ash according to ASTM C618 class F classification and is activated by sodium silicate (Na2SiO3) and sodium hydroxide (NaOH) solutions. The effects of molarities of NaOH, coarse aggregate sizes, duration of steam curing and extra added water on the compressive strength of geopolymer concrete at elevated temperatures are also presented. The results show that the fly-ash-based geopolymer concretes exhibited steady loss of its original compressive strength at all elevated temperatures up to 400 °C regardless of molarities and coarse aggregate sizes. At 600 °C, all geopolymer concretes exhibited increase of compressive strength relative to 400 °C. However, it is lower than that measured at ambient temperature. Similar behaviour is also observed at 800 °C, where the compressive strength of all geopolymer concretes are lower than that at ambient temperature, with only exception of geopolymer concrete containing 10 m NaOH. The compressive strength in the latter increased at 600 and 800 °C.The geopolymer concretes containing higher molarity of NaOH solution (e.g. 13 and 16 m) exhibit greater loss of compressive strength at 800 °C than that of 10 m NaOH. The geopolymer concrete containing smaller size coarse aggregate retains most of the original compressive strength of geopolymer concrete at elevated temperatures. The addition of extra water adversely affects the compressive strength of geopolymer concretes at all elevated temperatures. However, the extended steam curing improves the compressive strength at elevated temperatures. The Eurocode EN1994:2005 to predict the compressive strength of fly-ash-based geopolymer concretes at elevated temperatures agrees well with the measured values up to 400 °C.